Soil metagenomic analysis on changes of functional genes and microorganisms involved in nitrogen-cycle processes of acidified tea soils - Lin, Shunxian; Liu, Zhijun; Wang, Yuchao; Li, Jiayu; Wang, Gege; Ye, Jianghua; Wang, Haibin; He, Haibin (Frontiers in Plant Science, 2022)
Nitrogen (N) is the first essential nutrient for tea growth. However, the effect of soil acidification on soil N cycle and N forms in tea plantation are unclear. In this study, the nitrogen contents, soil enzyme activity and N mineralization rate in acidified soil of tea plantation were measured. Moreover, the effects of soil acidification on N cycling functional genes and functional microorganisms were explored by soil metagenomics. The results showed that the NH4+-N, available N and net N mineralization rate in the acidified tea soil decreased significantly, while the NO3--N content increased significantly. The activities of sucrase, protease, catalase and polyphenol oxidase in the acidified tea soil decreased significantly. The abundance of genes related to ammonification, dissimilatory N reduction, nitrification and denitrification pathway in the acidified tea soil increased significantly, but the abundance of functional genes related to glutamate synthesis and assimilatory N reduction pathway were opposite. In addition, the abundance of Proteobacteria, Actinobacteria, Chloroflexi, Nitrospirae, Actinomadura, Nitrospira etc. microorganisms related to nitrification, denitrification and pathogenic effect increased significantly in the acidified tea soil. The correlation results showed that soil pH and N forms were correlated with soil enzyme activity, N cycling function genes and microbial changes. In conclusion, soil acidification results in significant changes in enzyme activity, gene abundance and microorganism involved in various N cycle processes in acidified tea soil, which leads to imbalance of soil N form ratio and is not conducive to N transformation and absorption of tea trees.